Muslim Puritan Dan Muslim Moderat (Pembacaan Terhadap Kedudukan Perempuan) - Munawir, Munawir (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2017)
Puritans Muslim -with a spirit of the Quran and Sunnah- made Islam in the time of Prophet Sawas an authentic and final model. Using a textual approach, they understand Islam rigidly so that all the features of Islam mixed with local locality (non-Arabic) are considered to be viruses and must be sterilized to get pure. In contrast to moderate Muslims, though both of them are in line with the Qur'an and Sunnah, they are not using a textual approach but contextualist or even philosophical. Islam at the time of the Prophet saw was viewed by moderate Muslims as a historic and dialectical Islam with socio-cultural society, because they understand Islam flexibly. With different approaches in the return movement in the Quran and Sunnah, the two Islamic epistemes are different, as seen in the issue of women's position. In the history, Puritan Muslims often use violence in the name of religion to defend and spread its ideology. The above study is based on historical study with descriptive-qualitative approach.